1979
DOI: 10.1007/bf00254689
|View full text |Cite
|
Sign up to set email alerts
|

Collagenase ? A marker enzyme in human bladder cancer?

Abstract: Collagenase activity in human bladder carcinomas was measured against 14C-labeled collagen as substrate. Enzymes activity in vivo increased with the degree of penetration of the bladder wall. It was not detectable or low in the cases of superficially infiltrating tumours (A, B1 B2) and high in the cases of deeply infiltrating tumours (C, D). These results suggest that collagenase activity of advanced tumours is predominantly expressed in the pervesical layer of the bladder wall. A quantitative estimate of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
1

Year Published

1982
1982
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 26 publications
0
20
1
Order By: Relevance
“…The level of collagenase was found to correlate with the aggressiveness of the tumour (Wirl & Frick, 1979). A type IV collagenase was demonstrated in migrating endothelial cells and especially in metastatic tumour cells (Kalebic et al, 1983) and the amount of this enzyme was found to be increased in highly metastatic tumour cells .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The level of collagenase was found to correlate with the aggressiveness of the tumour (Wirl & Frick, 1979). A type IV collagenase was demonstrated in migrating endothelial cells and especially in metastatic tumour cells (Kalebic et al, 1983) and the amount of this enzyme was found to be increased in highly metastatic tumour cells .…”
Section: Resultsmentioning
confidence: 92%
“…While many reports noted elevated collagenase activities in human and animal tumours, Wirl and Frick (1979) found that collagenase activity in bladder tumour extracts increased with the degree of depth penetration.…”
mentioning
confidence: 84%
“…Treatment with 3 M NaSCN, that destroys complexes of ccz-macroglobulin in other systems [21], did not reveal collagenase activity in supernatants and extraction of the fibrous material of tumor homogenates with 5 M urea and ammonium sulfate precipitation was necessary to detect any collagenase, suggesting a high affinity of collagenase for its substrate. As for collagenase in extracts of other tissues [5,27], part of the total activity was latent and its activation was closely similar as it could be activated by trypsin, by prolonged storage at -20 "C or by preincubation at 37 'C without trypsin, causing an apparent autoactivation.…”
Section: Discussionmentioning
confidence: 87%
“…26,27 Bladder tumors that invade muscle display significantly higher collagenase activity than do their noninvasive counterparts. 28 Higher urinary MMP-1 expression has also been correlated with disease progression and poor survival in bladder cancer cases. 29 Collagenases (MMP-1 and -13) degrade several native fibril collagens, including types I, II and III, resulting in their cleavage.…”
Section: Cxcr4-mediated Pca Migration and Invasion S Singh Et Almentioning
confidence: 99%